Anti-inflamatory activity of the flowers of Gumamela (Hibiscus rosasinensis linn.) - Orzales, Charisse Mae Exmundo (2003.)
Four different color-varieties, red-single, red-double, white-single, flesh-single, of Hibiscus rosasinensis Linn. were screened for tehir anti-inflammatory activity. Of the four plants, the methanol extract of the dried flowers of the red-single hibiscus gave a promising potential for its ability to inhibit inflammation on Carrageenan-induced inflammation by 51.06%. The plant was further analyzed for the presence of alkaloids, results showed the absence of such phytochemicals., Isolation of the anti inflammatory constituents of the red-single hibiscus was done by concentrating the methanol extract in vacuo and sequentially extracted with pet ether, DCM and ethyl acetate. The ethly acetate fraction of the extract exhibited the highest anti-inflammatory activity of 84.04%, indicating that the bioactive constituent is likely polar in nature. VAcuum liquid chromatographic method further purified the ethyl acetate extract. TLC analysis has allowed fractions with relatively the same Rf values to be pooled together as one, using solvent system of pet ether: DCM: ethyl acetate (1:4:1) and vanillin-sulfuric as indicator. The resulting fractions E1 [Rf value of 0.972(Violet)], E2[Rf=0.056(yellow), 0.235(orange), 0.323(light orange)] and E3[Rf=0.152(orange), 0.215(grayish yellow)], were tested for inflammatory activity. Fraction E2 has the highest anti-inflammatory activity of 73.02% and was likely polar since it was eluted by DCM: Ethyl acetate (80:20) solvent system. The results also suggest that the flowers Hibiscus rosasinensis Linn. are potential anti-inflammagrn and bioactive component could be phenolic compounds such as flavonoids.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Flowers -- Gumamela